Reduced insulin action in muscle of high fat diet rats over the diurnal cycle is not associated with defective insulin signaling - Lewin Small; Amanda E. Brandon; Benjamin L. Parker; Vinita Deshpande; Azrah F. Samsudeen; Greg M. Kowalski; Jane Reznick; Donna L. Wilks; Elaine Preston; Clinton R. Bruce; David E. James; Nigel Turner; et al. (Elsevier, 2019)
Objective: Energy metabolism and insulin action follow a diurnal rhythm. It is therefore important that investigations into dysregulation of these pathways are relevant to the physiology of this diurnal rhythm. Methods: We examined glucose uptake, markers of insulin action, and the phosphorylation of insulin signaling intermediates in muscle of chow and high fat, high sucrose (HFHS) diet-fed rats over the normal diurnal cycle. Results: HFHS animals displayed hyperinsulinemia but had reduced systemic glucose disposal and lower muscle glucose uptake during the feeding period. Analysis of gene expression, enzyme activity, protein abundance and phosphorylation revealed a clear diurnal regulation of substrate oxidation pathways with no difference in Akt signaling in muscle. Transfection of a constitutively active Akt2 into the muscle of HFHS rats did not rescue diet-induced reductions in insulin-stimulated glucose uptake. Conclusions: These studies suggest that reduced glucose uptake in muscle during the diurnal cycle induced by short-term HFHS-feeding is not the result of reduced insulin signaling. Keywords: Insulin action, Glucose uptake, Skeletal muscle, Insulin signaling, Diurnal rhythms, Phosphoproteomics